1986
DOI: 10.1079/bjn19860108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manipulating growth in sheep by diet or anabolic agents on plasma cortisol and muscle glucocorticoid receptors

Abstract: I. The cortisol status (total plasma cortisol concentration, free cortisol concentration, transcortin capacity) and the characteristics of skeletal muscle binding for cortisol and dexamethasone were examined in female lambs either implanted with Zeranol or trenbolone acetate or whose dietary intake was restricted.2. The skeletal muscle glucocorticoid receptor had a high affinity for the glucocorticoid triamcinolone (relative binding affinity 0.85) and cortisol (relative binding affinity 0.51) with virtually no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Down-regulation of GR expression mediated by androgens has been observed in the hippocampal pyramidal cell layer of CA1 neurons (Kerr et al 1996) and rat motor neurons (Blanco et al 2002). In muscle, it has been shown that treatment of sheep with trenbolone also reduces GR expression (Sharpe et al 1986).…”
Section: Insulin-like Growth Factor-imentioning
confidence: 96%
“…Down-regulation of GR expression mediated by androgens has been observed in the hippocampal pyramidal cell layer of CA1 neurons (Kerr et al 1996) and rat motor neurons (Blanco et al 2002). In muscle, it has been shown that treatment of sheep with trenbolone also reduces GR expression (Sharpe et al 1986).…”
Section: Insulin-like Growth Factor-imentioning
confidence: 96%
“…As summarized by Hickson et al, 43 both in vitro and in vivo studies have failed to show a consistent positive interaction of these steroids with the glucocorticoid receptors in muscle. Sharpe et al 44 postulated that AASs do not occupy glucocorticoid receptor sites but down-regulate the glucocorticoid receptor content. Indirect evidence of an antiglucocorticoid e¡ect in humans comes from a case study in which a patient with androgen insensitivity syndrome received pharmacological doses of T enanthate (5 mg/kg/day for 10 days).…”
Section: Anabolic Androgenic or Anticatabolic Action?mentioning
confidence: 99%
“…If this situation is analogous to the human, then it is possible that the large increase in T secretion observed during puberty in young men causes down-regulation of receptors in skeletal muscles. After puberty, the receptors in these muscles would be saturated by T; therefore administration of supratherapeutic doses of T or synthetic AASs would 44 postulated that AASs do not occupy glucocorticoid receptor sites but down-regulate the glucocorticoid receptor content. Indirect evidence of an antiglucocorticoid e¡ect in humans comes from a case study in which a patient with androgen insensitivity syndrome received pharmacological doses of T enanthate (5 mg/kg/day for 10 days).…”
Section: Anabolic Androgenic or Anticatabolic Action?mentioning
confidence: 99%
“…However, the mech anisms by which anabolic steroids increase muscle protein content are unclear. They may act directly on muscle [10], or indirectly by inhibition of glucocorticoid action either by modification of adrenal activity [ 11 ], by com petition for the receptor binding sites of glu cocorticoids [12], or by reduction of the den sity of glucocorticoid receptors [13], The effect of anabolic steroids on muscle protein turnover is controversial. In animal studies, testosterone propionate has been shown to increase the rates of muscle protein synthesis and degradation [14] whereas trenbolone acetate decreases both parameters [15,16], Another anabolic steroid, stanozolol, increases muscle protein synthesis while protein degradation is not affected [ 17].…”
Section: Introductionmentioning
confidence: 99%